Serodiagnosis of Primary Infections with Human Parvovirus 4, Finland - Lahtinen, Anne (Centers for Disease Control and Prevention, 2011)
To determine the prevalence of parvovirus 4 infection and its clinical and sociodemographic correlations in Finland, we used virus-like particle–based serodiagnostic procedures (immunoglobulin [Ig] G, IgM, and IgG avidity) and PCR. We found 2 persons with parvovirus 4 primary infection who had mild or asymptomatic clinical features among hepatitis C virus–infected injection drug users.